The Influence of Delivery Timeliness, Perceived Packaging Price, and Packaging Quality on Customer Satisfaction: A Case Study of J&T Express, East Jakarta Branch 2024 - Erwin R. Manurung; Azmieti Kurnia Sinta; Atika Liona Kurnia; Amalia Putri Dinova (Whoosh: Journal of Transportation and Logistic, 2026)
J&T Express is one of the courier companies in Indonesia that has the desire to continuously improve the quality of its services. The problem that often occurs at the East Jakarta branch of JNT Express is that the package does not arrive (kompas.id, listed June 22, 2024). This study aims to determine the effects of Delivery Timeliness, Perceived Packaging Price, and Packaging Quality on Customer Satisfaction at PT J&T Express, East Jakarta branch. The population in this study were 50,000 consumers of J&T East Jakarta branch with a sample of 50 consumers based on the slovin formula. This study uses primary data with data collection methods through questionnaires distributed to 50 respondents. This research approach uses quantitative with data analysis techniques using multiple linear regression analysis and using the SPSS version 25.0 program.